2004
DOI: 10.1093/jxb/erh247
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the role of the major proteinases of germinated common bean (Phaseolus vulgaris L.) and soybean (Glycine max (L.) Merrill) seeds in the degradation of their storage proteins

Abstract: Two types of cysteine proteases, low-specificity enzymes from the papain family and Asn-specific from the legumain family are generally considered to be the major endopeptidases responsible for the degradation of seed storage proteins during early seedling growth. The action of the corresponding enzymes (CPPh1 and LLP, respectively) from common bean (Phaseolus vulgaris L.) on phaseolin (the common bean storage protein), and on the homologous soybean (Glycine max (L.) Merrill) storage protein, beta-conglycinin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…During germination, the proteins started to be degraded by endopeptidases, located in the cotyledons, forming oligopeptides. The oligopeptides are then hydrolyzed by exopeptidases in order to form free amino acids, which will be used to synthesize new proteins and tissues (Sangronis et al, 2006;Zakharov et al, 2004).…”
Section: Soluble Protein and Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…During germination, the proteins started to be degraded by endopeptidases, located in the cotyledons, forming oligopeptides. The oligopeptides are then hydrolyzed by exopeptidases in order to form free amino acids, which will be used to synthesize new proteins and tissues (Sangronis et al, 2006;Zakharov et al, 2004).…”
Section: Soluble Protein and Antioxidant Capacitymentioning
confidence: 99%
“…During germination, several biochemical mechanisms are activated such as the hydrolysis of starch and proteins, in order to meet the needs of the new plant (Klose & Arendt, 2012). Endopeptidases degrade storage proteins producing oligopeptides, which are further degraded by exopeptidases forming free amino acids (Sangronis, Rodríguez, Cava, & Torres, 2006;Zakharov, Carchilan, Stepurina, Rotari, Wilson, & Vaintraub, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4, 5), it can be suggested that there seems to exist synthesis de novo of some proteases during and after germination, which are necessary to the storage protein mobilisation. Proteases are involved in the storage proteins hydrolyses and many of these enzymes are synthesised de novo during and after germination (Cervantes et al 1994;Bewley 1997;Asano et al 1999;Buckeridge et al 2004b;Zakharov et al 2004). In seeds of tomato, it has been observed that the actinomycin-D inhibits the proteases activities during the post-germinative process (Mathan 1965).…”
Section: Storage Proteins Mobilisationmentioning
confidence: 99%
“…Proteolytic enzymes are intricately involved in many aspects of plant physiology and development [2,4]. Numerous reports including our previous data supported that the proteases are responsible for protein degradation [5][6][7][8][9][10]. With renewed interest, there has been proliferation of reports in the last decade concerning purification and characterization of these proteases from leguminous and nonleguminous seeds [2,[11][12][13][14][15][16].…”
mentioning
confidence: 98%